Small animal internal medicine (Elsevier/Mosby, 2014)
With hundreds of images and a practical clinical emphasis, Small Animal Internal Medicine, 5th Edition helps you recognize, diagnose, and treat common internal disorders and conditions. Clear, step-by-step guidelines thoroughly describe commonly performed procedures. Hundreds of summary tables make it easy to look up clinical signs, potential causes, drug information, and treatment modalities. This edition is updated with the latest research findings for accurate diagnosis and management of small animal pathologies. Written by veterinary clinicians Richard Nelson and C. Guillermo Couto, and joined by a team of expert contributors, this text is a comprehensive, easy-to-read guide to solving internal medical challenges.